2022
DOI: 10.1101/2022.02.04.479111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Motivational trade-offs in bumblebees

Abstract: Mammals can supress their nociceptive responses to prioritise other important responses via endogenous modulation from the brain. It is well established that insects display nociception, but not whether the insect brain can modulate nociceptive processing. To address this question, we investigated whether bumblebees′ (Bombus terrestris) attraction to higher sucrose solution concentrations reduces their avoidance of noxious heat. Bees were given the choice between either unheated or noxiously-heated (55°C) feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the theory defended here we might thus see a valence system as the revolution needed to make animal agency "pay off," providing an efficient action selection mechanism as the final behavioral common path of metazoans for the prioritization of some actions over others in the complexity increase of more degrees of freedom. 25 What evidence has been gathered in invertebrates is highly suggestive that this is not a unique vertebrate trait (Gibbons et al 2022). If not for the the possibility of pain in ants, bees, flies, and the like makes sense in the context of their robotic, short, and fast lives (Veit 2022e).…”
Section: The Dawn Of Consciousness Explainedmentioning
confidence: 99%
“…In the theory defended here we might thus see a valence system as the revolution needed to make animal agency "pay off," providing an efficient action selection mechanism as the final behavioral common path of metazoans for the prioritization of some actions over others in the complexity increase of more degrees of freedom. 25 What evidence has been gathered in invertebrates is highly suggestive that this is not a unique vertebrate trait (Gibbons et al 2022). If not for the the possibility of pain in ants, bees, flies, and the like makes sense in the context of their robotic, short, and fast lives (Veit 2022e).…”
Section: The Dawn Of Consciousness Explainedmentioning
confidence: 99%
“…Indeed, on February 8 this year, a particularly compelling preprint on motivational trade-offs in bumblebees was uploaded by Lars Chittka's bee lab (see Gibbons et al 2022). In it, the authors showed that bees when faced with noxiously heated feeders and different sugar concentrations could trade off "competing conditioned motivational stimuli to modulate nocifensive behaviour" which they argued would suggest "a form of pain perception" (Gibbons et al 2022, p. 1).…”
Section: Evaluative Experiencementioning
confidence: 99%
“…It seems likely that the confluence of these signals is necessary for aesthetic appreciation, and moreover, that similar systems exist in other animals who share our evolutionary neurobiological roots. Research by Gibbon et al ( 49 ) indicates that bees can modulate their nociceptive responses to prioritize feeding, which suggests that these are insects capable of perceiving pain. If so, does this point to a capacity for also experiencing pleasure?…”
Section: Perception Aesthetic Sensibility and Behaviormentioning
confidence: 99%